High‐Accuracy Near‐Infrared Carbon Dioxide Intensity Measurements to Support Remote Sensing. Issue 5 (10th March 2020) - Long, D. A.; Reed, Z. D.; Fleisher, A. J.; Mendonca, J.; Roche, S.; Hodges, J. T.
Abstract: Two cavity ring‐down spectrometers were employed to accurately measure line intensities in a series of near‐infrared carbon dioxide bands including (30012) ← (00001), (30013) ← (00001), and (30014) ← (00001) near 1.6 μm. Relative combined standard uncertainties for these band intensities were less than 0.1% and showed significant, percent‐level deviations with respect to many existing spectroscopic databases (although close agreement was observed with the HITRAN 2016 database in the (30013) ← (00001) and (30014) ← (00001) bands). Further, the resulting line intensities were utilized in Total Carbon Column Observing Network retrievals and led to significantly reduced biases in the (30012) ← (00001) and (30013) ← (00001) bands. These results indicate that refinements of spectroscopic databases are required to meet the accuracy targets of both ground‐ and satellite‐based remote sensing missions. Key Points: Near‐infrared CO2 line intensities measured with combined standard uncertainties below 0.1% Deviations in excess of 1% were found between these measurements and existing databases These new intensities led to reduced biases in atmospheric retrievals of CO2 mixing ratios when using two near‐infrared bands